1992
DOI: 10.1038/jcbfm.1992.28
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Consumption of the Living Human Brain Measured after a Single Inhalation of Positron Emitting Oxygen

Abstract: Summary:We measured the rate of washout of 150_ labeled water generated from labeled oxygen accumu lated in brain after bolus [150]02 inhalation, and com pared the washout with that of labeled water measured with H2150. Contrary to the original expectation, the ra dioactive water generated from labeled oxygen failed to leave the brain tissue at the rate predicted by exogenous water. Therefore, the use of a separately measured value for exogenous water clearance led to an error in the cal culation of oxygen con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
129
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(131 citation statements)
references
References 26 publications
(13 reference statements)
2
129
0
Order By: Relevance
“…Finally, it allows evaluation of coupling or uncoupling of CBF and CMRO 2 during functional activation or pharmacological stress, such as that induced by acetazolamide used for assessment of cerebral vascular reserves. Ohta et al (1992) showed another technique for the rapid estimation of CBF, OEF, and CMRO 2 from a 3-min single PET scan following bolus inhalation of 15 O 2 . This approach does not take into account recirculating water and involves a mathematical formula with weighted integration to calculate these quantitative values.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, it allows evaluation of coupling or uncoupling of CBF and CMRO 2 during functional activation or pharmacological stress, such as that induced by acetazolamide used for assessment of cerebral vascular reserves. Ohta et al (1992) showed another technique for the rapid estimation of CBF, OEF, and CMRO 2 from a 3-min single PET scan following bolus inhalation of 15 O 2 . This approach does not take into account recirculating water and involves a mathematical formula with weighted integration to calculate these quantitative values.…”
Section: Discussionmentioning
confidence: 99%
“…There have been other attempts to obtain CBF and CMRO 2 images more rapidly (Huang et al, 1986;Holden et al, 1988;Meyer et al, 1987;Ohta et al, 1992;Ho and Feng, 1999). Mathematical refinement has allowed images to be generated from data from a single scan alone on a bolus inhalation of 15 O 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O (Ohta et al, 1992). The O 15 O raw images (voxel size: 1.471 Â 1.471 Â 2.45 mm 3 ) were smoothed using a three-dimensional filter (in plane full-width at half-maximum = 2.942 mm, axial full-width at half-maximum = 2.45 mm) before OEF images were generated on a voxel basis.…”
mentioning
confidence: 99%
“…57,65 This could further reduce the diffusion distances within the same CMRO 2 measurement time. Therefore, the diffusion of H 2 17 O in the brain tissue is unlikely to be the major factor limiting spatial resolution of 17 17 O CSI in the human brain at 7 T using a 7.5 cm diameter surface coil with temporal resolution of 11 s and voxel size of 3.5 ml.…”
mentioning
confidence: 99%